YSH-134 A SWEET STALK SORGHUM HYBRID WITH HIGH POTENTIAL FOR SILAGE PRODUCTION IN PLAINS OF PUNJAB - JAVED, HM; SAEED, M; HAQ, IU; SHAIKH, GY; SADDAM, S; AWAIS, M; IQBAL, N; ASLAM, M; ZULIFQAR, W; ASIF, Z; MURTAZA, G (Biological and Clinical Sciences Research Journal, 2024)
Ever-increasing population and the impact of high heat, a combination of both diminishing factors place agricultural productivity at risk. Food security is current alarming issue and ringing the bells on the door of stakeholders including breeders to devise appropriate strategies for future needs. The development of hybrids in crops is the only tool to enhance productivity by 2-3 times folds than current potential. The livestock industry is also increasing steeply to meet dairy-related needs and requires high fodder-yielding hybrids to fulfill its functional tasks. The constitution of new and dual-purpose high-yielding sorghum hybrids is a core need to boost production potential in fodder crops. Sorghum provides highly nutritious grain and green parts and requires a limited input supply when compared to other crops. A great improvement potential is present in sorghum crops in terms of hybrid development. Here, this work was performed for the development of a new sorghum hybrid through the ABR system. YSH-134 is a cross combination between CMS-10A and YSS-98 with a higher grain (5000 kg/ha) and fodder (45000 kg/ha) yield potential. This hybrid was tested against the previously released sorghum hybrid Fakhar-e-Punjab. It’s the second of its lot and has yield superiority over check hybrid. YSH-134 maintained 3% and 15% yield enhancement at station trials during 2018 and 2020 over check hybrid. Under National Uniform Yield Testing, it showed more prominent and higher yield benefits (19% and 34% during 2019 and 2020, respectively) against its competitor. ANOVA and after ANOVA analysis showed its 14% grain yield increase and 26% fodder production than Fakhar-e-Punjab. This high productivity is owing to the exploitation of heterosis effects lying under this unique cross combination. High-yielding YSH-134 has a highly sweet and juicy stem (15% brix value) with green and broad which can be used as green fodder for the cattle and dairy industry. This work will pave the way to meet future targets through utilizing heterosis breeding and hybrid seed technology. This may help the researcher in designing breeding programs for the development of hybrids for higher yields in green fodder.